2006
DOI: 10.1093/sleep/29.7.890
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Multiple Sleep-Onset REM Periods in a Population-Based Sample

Abstract: The overall prevalence of 2 or more SOREMPs in our sample is 3.9%. Interestingly, of the variables assessed (MSLT, Epworth Sleepiness Scale, and total sleep time from nocturnal polysomnography), objective sleepiness, as determined by the MSLT, was the only measure significantly associated with 2 or more SOREMPs. Therefore, subpopulations with excessive sleepiness (eg, shift workers, young adults, patients with apnea) are likely to have a greater prevalence of SOREMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 25 publications
5
60
1
1
Order By: Relevance
“…Our data show a lower prevalence of C− over C+, in line with most clinical studies 8 22 23. However, recent data on adult populations demonstrated that a high prevalence of EDS combined with MSLT abnormalities is compatible with a diagnosis of C− 24 25…”
Section: Discussionsupporting
confidence: 91%
“…Our data show a lower prevalence of C− over C+, in line with most clinical studies 8 22 23. However, recent data on adult populations demonstrated that a high prevalence of EDS combined with MSLT abnormalities is compatible with a diagnosis of C− 24 25…”
Section: Discussionsupporting
confidence: 91%
“…Healthy subjects with multiple SOREMs were sleepier [35,36,37] than subjects with 1 or no SOREM. None of the 11 patients with MSL ≤5 min presented with SOREM.…”
Section: Discussionmentioning
confidence: 99%
“…Age and sex have already been shown to influence NPSG REML in patients with narcolepsy and controls 5,3335 ; we therefore matched patients and controls for these variables before comparisons. As a consequence, the total number of patients and controls was reduced to 516 pairs (some patients did not have a matching control).…”
Section: Methodsmentioning
confidence: 99%